2016
DOI: 10.15625/0866-708x/54/4/7356
|View full text |Cite
|
Sign up to set email alerts
|

Application Gis and Webgis Technology for Biodiversity Information Management a Case Study in Xuan Lien Nature Reserve

Abstract: Resource management in National parks (NP), Nature reserve (NR) aim to hold the status of biological resources of the area [4]. Up to now, Vietnam has established 31 NP and about 100 NR. Most of NR, NP was completed build biological database [4]. The traditional information sharing method has showed the limitations, causing many difficulties for the users, particularly when exploring the map information. WebGIS technology developed quickly with the functions included: internet access, query spatial data in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The results showed that the dust concentration exceeded 2 times comparison with the dust permission threshold of surrounding environment due to the emission from the Da Nang Steel Mill. This consequence was due to the plant's chimney height not meeting the allowable emission standards [5].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the dust concentration exceeded 2 times comparison with the dust permission threshold of surrounding environment due to the emission from the Da Nang Steel Mill. This consequence was due to the plant's chimney height not meeting the allowable emission standards [5].…”
Section: Introductionmentioning
confidence: 99%